(untitled) (TAJ: Journal of Teachers Association, 2020)
A 42-year-old adult schizophrenic patient developed high fever (106 degree Fahrenheit), mental state changes and muscle rigidity after treatment with parenteral haloperidol. Neuroleptic malignant syndrome (NMS) associated with haloperidol was suspected. Other differentials were excluded. Haloperidol was discontinued and prompt treatment with bromocriptine and lorazepam was started resulting in a good recovery. Because of the temporal relationship between the patient’s improvement with the discontinuation of haloperidol and treatment with lorazepam and bromocriptine, the diagnosis was believed to be haloperidol-induced NMS. TAJ 2019; 32(2): 62-63